Highly effective and CO-tolerant PtRu electrocatalysts supported on poly(ethyleneimine) functionalized carbon nanotubes for direct methanol fuel cells - Cheng, Y.; Jiang, San Ping (Pergamon, 2013)
A highly efficient and CO tolerant PtRu electrocatalysts supported on amino-rich, cationicpoly(ethyleneimine) polyelectrolyte functionalized multi-walled carbon nanotubes (PtRu/PEI-MWCNTs)has been developed. The catalysts were characterized by thermogravimetric analysis, Raman spectroscopy, cyclic voltammograms, CO stripping, chronoamperometry, transmission electron microscopy (TEM) and X-ray diffraction (XRD). The PtRu particles with average size ~2.5 nm are well dispersed on PEI-MWCNTs. The peak current for the methanol oxidation reaction on 40% PtRu/PEI-MWCNTs is 636 mA mg-1 Pt , 5.7 times higher than 112 mA mg-1 Pt measured on the 40% PtRu supported on acid treated MWCNTs (PtRu/AO-MWCNTs) under identical conditions. PtRu/PEI-MWCNTs catalysts exhibit a superior electrocatalytic activity and stability for the methanol oxidation reaction due to its high tolerance toward CO poisoning as compared with PtRu/AO-MWCNTs for direct methanol fuel cells.